Subcellular Localization and Activity of TRPM4 in Medial Prefrontal Cortex Layer 2/3 - Riquelme, Denise; Silva, Ian; Philp, Ashleigh M.; Huidobro-Toro, Juan P.; Cerda, Oscar; Trimmer, James S.; Leiva-Salcedo, Elias (Frontiers in Cellular Neuroscience, 2018)
TRPM4 is a Ca2+-activated non-selective cationic channel that conducts monovalent cations. TRPM4 has been proposed to contribute to burst firing and sustained activity in several brain regions, however, the cellular and subcellular pattern of TRPM4 expression in medial prefrontal cortex during postnatal development has not been elucidated. Here we use multiplex immunofluorescence labeling of brain sections to characterize the postnatal developmental expression of TRPM4 in the mouse medial prefrontal cortex. We also performed electrophysiological recordings to correlate the expression of TRPM4 immunoreactivity with the presence of TRPM4-like currents. We found that TRPM4 is expressed from the first postnatal day, with expression increasing up to postnatal day 35. Additionally, in perforated patch clamp experiments, we found that TRPM4-like currents were active at resting membrane potentials at all postnatal ages studied. Moreover, TRPM4 is expressed in both pyramidal neurons and interneurons. TRPM4 expression is localized in the soma and proximal dendrites, but not in the axon initial segment of pyramidal neurons. This subcellular localization is consistent with a reduction in the basal current only when we locally perfused 9-Phenanthrol in the soma, but not upon perfusion in the medial or distal dendrites. Our results show a specific localization of TRPM4 expression in neurons in the medial prefrontal cortex and that a 9-Phenanthrol sensitive current is active at resting membrane potential, suggesting specific functional roles in medial prefrontal cortex neurons during postnatal development and in adulthood.